Rapid detection of Pseudo-nitzschia species using whole-cell fluorescence in situ Hybridization (FISH) - Lim, Lay Peng (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The genus Pseudo-nitzschia comprised of thirty-four known species with half of them is reported to produce domaic acid (DA), a neurotoxin associated with Amnesic Shellfish Poisoning (ASP). Species identification of Pseudo-nitzschia mainly depends on detailed observations of the fine ultrastructure of frustules which cannot be easily distinguishable without electron microscope. In this study, a molecular approach for rapid detection of Pseudo-nitzschia spp. by using whole-cell fluorescence in situ hybridization (FISH) was developed. Cultured and natural samples of Pseudo-nitzschia used in this study were identified by transmission and scanning electron microscopy (TEM & SEM). Species specific oligonucleotide probes were designed in silico to P. pungens (L-S-P.pu-0378-a-A-23), P. brasiliana (L-S-P.br-0129-a-A-23) and P. galaxiae (L-S-P.ga-0128-a-A-23) based on sequences obtained in this study and SILVA database. Synthesized P. pungens specie specific PuD1 probe was applied on both cultured and field samples with UniC and UniR probe used as positive and negative control. Efficiency of PuD1 probe in detection was consistently more than 93%. Probe PuD1 coupled with FISH method is equally efficiency in cell enumeration compared to traditional method with low discrepancy (<20%). This rapid detection method should be adopted in the HABs monitoring program for detection of harmful and potential harmful species of Pseudonitzschia.